2001
DOI: 10.1111/j.1574-6968.2001.tb10516.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular approach to the characterisation of fungal communities: methods for DNA extraction, PCR amplification and DGGE analysis of painted art objects

Abstract: A protocol for efficient extraction of fungal DNA from micromycetes colonising painted art objects was developed. Polymerase chain reaction (PCR) inhibitors were successfully removed by a combined application of a Chelex-100 adsorption resin and a Geneclean Kit for Ancient DNA. Universal fungal primers for PCR amplification of 28S rDNA (U1 and U2) were tested for their applicability in denaturing gradient gel electrophoresis (DGGE) analysis of fungal communities. Artificially produced mortar samples inoculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 14 publications
(16 reference statements)
2
34
0
1
Order By: Relevance
“…capabilities may grow or survive [52] [53]. These requirements coincide with the physiological characteristics of some microorganisms detected in this study, as mentioned above.…”
Section: Discussionsupporting
confidence: 87%
“…capabilities may grow or survive [52] [53]. These requirements coincide with the physiological characteristics of some microorganisms detected in this study, as mentioned above.…”
Section: Discussionsupporting
confidence: 87%
“…The forward primer employed was Fung-GC, and the reverse primer was NS1 (Table 1) [23]. A total of 25  μ L of PCR mixture contained 1 × Ex Taq PCR buffer with MgCl 2 , 100  μ M dNTP, 0.5  μ M of each of the primers, 1U Ex Taq DNA polymerase (Takara), and 50 ng DNA template.…”
Section: Methodsmentioning
confidence: 99%
“…Selected DNA fragments were excised from the DGGE gel and submerged overnight at 4°C in 100  μ L TE buffer. A PCR based on a 1  μ L aliquot of the gel fragment extract as template was performed under the same conditions as described above, with the Fung primer replacing Fung-GC as the forward primer (Table 1) [23]. The resulting amplicons were purified using a Biospin Gel Extraction kit (BioFlux, China) and cloned into the pMD19-T vector (Takara) for sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, ITS sequences vary not only regarding the order of the nucleotides but also their length. For this reason, sequences from the 18S region (Gomes et al 2003;Kowalchuk et al 1997;Pennanen et al 2001;Prakitchaiwattana et al 2004;Smit et al 1999;Vainio and Hantula 2000;Van Elsas et al 2000) or from the 26S region (Cocolin et al 2000;Möhlenhoff et al 2001;Prakitchaiwattana et al 2004) are frequently used. We chose the primer pair published by Cocolin et al (2000) to amplify fragments in the variable D1 region.…”
Section: Comparison Of the Methods Usedmentioning
confidence: 98%
“…Some years later, this method has been used for the direct characterization of fungi (Gomes et al 2003;Kowalchuk et al 1997;Möhlenhoff et al 2001;Pennanen et al 2001;SchabereiterGurtner et al 2001;Smit et al 1999;Vainio and Hantula 2000;Van Elsas et al 2000) and yeast populations (Cocolin et al 2000(Cocolin et al , 2002Prakitchaiwattana et al 2004). Recently, several authors have suggested combining cloning and DGGE to overcome the disadvantages of these methods (Gomes et al 2003;Möhlenhoff et al 2001;SchabereiterGurtner et al 2001). Gomes et al (2003) also recommended the combination of both cultivation-independent and cultivation-dependent approaches, to gain better insights in fungal biodiversity.…”
Section: Introductionmentioning
confidence: 94%